2009
DOI: 10.1016/j.jtcvs.2008.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Toward a new cold and warm nondepolarizing, normokalemic arrest paradigm for orthotopic heart transplantation

Abstract: A new nondepolarizing, normokalemic adenosine-lidocaine arrest solution in Krebs-Henseleit buffer with 10-mmol/L glucose was versatile at both 4 degrees C and 28 degrees C to 30 degrees C relative to Celsior, and the addition of 1-mmol/L pyruvate significantly improved cardiac output at warmer arrest temperatures. This new arrest paradigm may be useful in the harvest, storage, and implantation of donor hearts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…Only hearts that met the following predetermined baseline criteria were used in this study: heart rate greater than 200 bpm, regular rhythm, cardiac output greater than 25 mL/min, and coronary flow greater than 10 mL/ min. 22 After the baseline working heart period, hearts were arrested with cardioplegia as described later, and then exposed to ambient room temperature (22 CÀ23 C) for a 60-minute ischemic period. Reperfusion began with retrograde perfusion at 4 mL/min and increased in 0.5-mL/min increments every 30 seconds to 10 mL/min.…”
Section: Isolated Working Heartmentioning
confidence: 99%
“…Only hearts that met the following predetermined baseline criteria were used in this study: heart rate greater than 200 bpm, regular rhythm, cardiac output greater than 25 mL/min, and coronary flow greater than 10 mL/ min. 22 After the baseline working heart period, hearts were arrested with cardioplegia as described later, and then exposed to ambient room temperature (22 CÀ23 C) for a 60-minute ischemic period. Reperfusion began with retrograde perfusion at 4 mL/min and increased in 0.5-mL/min increments every 30 seconds to 10 mL/min.…”
Section: Isolated Working Heartmentioning
confidence: 99%
“…Nearly 40% of AL (0.1 mM K + ) and 25 mM K + alone hearts failed to return HR, developed pressures or CO after 1 h arrest at 32–33°C. In 2009, Rudd and Dobson advanced the AL cardioplegic concept as a new paradigm for orthotopic heart transplantation, and showed that arrest and reanimation was versatile at both cold (4°C) and warmer (28–30°C) temperatures compared with Celsior solution (Rudd and Dobson, 2009). In 2011, Rudd and Dobson further showed that the rat heart could be placed in suspended animation with AL, insulin and melatonin for 8 h in cold static storage (4°C) and returned 80% of left ventricular function compared to two FDA approved preservation solutions, Custodiol-HTK and Celsior, that could barely return 10% left ventricular function (Rudd and Dobson, 2011b).…”
Section: Adenosine Lidocaine and Mg2+ (Alm™): A More Natural Way Tomentioning
confidence: 99%
“…Its role in heart preservation is currently being investigated. Results from Dobson et al showed favourable recovery of cardiac parameters after six hours of cold storage in AL solution [67,68].…”
Section: Organ Preservationmentioning
confidence: 99%